Knowledge and attitudes regarding medication errors among nurses: a cross-sectional study in major Jeddah hospitals - Alandajani, Alham; Khalid, Bahariah; Ng, Yee Guan; Banakhar, Maram (Multidisciplinary Digital Publishing Institute, 2022)
Medication error is a multifactorial problem that mainly involves missing or bypassing the administration, which may have life-threatening impacts on the patient. Nevertheless, there is a dearth of information on medication errors among nurses in Saudi Arabia. This study investigates the knowledge and attitudes toward medication errors and their associated factors among nurses in Saudi Arabia. A cross-sectional study was conducted in four major public hospitals by recruiting a total of 408 nurses using cluster random sampling and proportional stratified sampling techniques. Data were gathered using an online self-administered questionnaire from January to March 2022. Descriptive statistics, Chi-square tests, and binary logistic regression models were performed to analyze the data. The prevalence of medication error among the nurses was 72.1%, only 41.2% were reported, while wrong doses (46.9%) were the most common type of medication error. Approximately 55% and 50% of the respondents demonstrated good knowledge and a positive attitude toward medication errors, respectively. The prevalence of medication error was associated with age groups of less than 25, and 25–35 years old, King Fahad and King Abdulaziz hospitals, no history of attending an MER training course, poor knowledge, and negative attitude. These findings reflect a high prevalence of medication error among nurses in Saudi Arabia, and the factors identified could be considered in mitigating this important health problem.